Place naming in the Limpopo - Sebashe, Setimela Samson (My University, 2003)
Refer to document
Thesis (M. A. (African Languages)) -- University of Limpopo, 2003
Keywords: Place renaming; Names, (Geographical) -- South Africa -- Limpopo